2022
DOI: 10.3390/healthcare10071301
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Low-Level Laser Therapy Combined with Single Flap Periodontal Surgery in the Management of Intrabony Periodontal Defects: A Randomized Controlled Trial

Abstract: This study aimed at assessing the clinical outcomes of the Single Flap Approach (SFA) with the additional use of Low-level laser therapy (LLLT). The defects were treated as per the principles of SFA, whereby 20 defects received only SFA (control group) and 20 defects received additional LLLT for bio stimulation/bio modulation (test group). Stable primary closure of the flaps was obtained with vertical internal mattress sutures. Plaque indices (FMPS), clinical attachment levels (CAL), probing pocket depth (PPD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Wound healing is a complex process that involves the proliferation, differentiation, migration, and adhesion of various cell types. Different growth factors regulate the functions of these cells, which ultimately determine the rate and quality of healing [ 21 ]. Diode lasers exert additional effects on fibroblasts by promoting proliferation, increasing cell number, secreting growth factors, and differentiating fibroblasts into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing is a complex process that involves the proliferation, differentiation, migration, and adhesion of various cell types. Different growth factors regulate the functions of these cells, which ultimately determine the rate and quality of healing [ 21 ]. Diode lasers exert additional effects on fibroblasts by promoting proliferation, increasing cell number, secreting growth factors, and differentiating fibroblasts into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is an inflammatory disease of the gingiva and periradicular tissues initiated by pathogenic bacteria present in biofilms, releasing enzymes and triggering an immune mechanism, causing host-parasite interaction and subsequently, loss of attachment and bone loss [27] . It was found that if proper parameters are used when incorporating LLLT treatment such as photodynamic therapy they can be useful as an alternative therapy for periodontal disease [28] .…”
Section: Periodonticsmentioning
confidence: 99%
“…Além disso, inúmeros moduladores como a terapia a laser de baixa intensidade (LLLT) se tornaram ferramentas adjuvantes e bem aceitas na cicatrização das feridas, fazendo com que o comportamento das células seja alterado pela irradiação em um comprimento de onda específico (WALSH, 1997;ROCHA JÚNIOR et al, 2006;SILVIYA et al, 2022). Com isso, o metabolismo celular e a proliferação aumentam, otimizando assim o reparo tecidual.…”
unclassified
“…Com isso, o metabolismo celular e a proliferação aumentam, otimizando assim o reparo tecidual. Deste modo, a LLLT se torna efetivo devido às suas propriedades físicas, bactericidas, anti-inflamatórias, analgésicas, de estimulação celular, de ablação e de proliferação (YAMADA, 1991;TADAKUMA, 1993;SILVA NETO et al, 2020;SILVIYA et al, 2022).…”
unclassified